MANAGING THE BUILDING DESIGN PROCESS FOR SUSTAINABILTY AND IMPROVED QUALITY - Joseph A. Fadamiro; Sunday Bobadoye (Institute of Research and Community Outreach - Petra Christian University, 2006)
The essence of building design process and management for building sustainability in the creation and maintenance of a qualitative architectural product is investigated in this paper. The design process, concept of building sustainability and particularly the quality of the built environment are discussed. Akure, a state capital in Nigeria was used as a case study. The principles and indicators for sustainability of buildings and its implications on the quality of the environment are examined in details. Survey findings include the views of the professionals on the clients, perception on the design process as well as management of projects, and the implications on the quality of the ensuring products and the cityâs environment. The data were factor analyzed using varimax rotation criterion (with Kaiser Normalization). The results revealed that five factors were effective, with one of them exhibiting the greatest variability and individual differences. The variables that loaded on this factor were really the aspects of the process and management relating to the clients. The findings also revealed the professionalsâ wrong attitude towards design process as shown with a very high degree of variability in the study. The paper concludes by recommending the enactment and enforcement of relevant policies with adequate education of the people and the involvement of all the stakeholders in the management of building projects and environmental programmes for the realization of a qualitative architectural product.